The effectiveness of online supervision for postgraduate students: a systematic literature review - Farah Shafilla Mohamad Kasim,; Bahbibi Rahmatullah,; Hussin Khan Rahmatullah Khan,; Ahmad Nurzid Rosli,; Noor Hidayah Che Lah,; Hidayanto, Achmad Nizar; Matthíasdóttir, Asrun (Penerbit Universiti Kebangsaan Malaysia, 2023)
The adoption of the most recent information and communication technology has led to changes in supervision methods, with online supervisory processes replacing face-to-face approaches. A systematic literature review (SLR) was used to explore the effectiveness of online supervision for postgraduate students. The PRISMA statement (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) recommendations were followed during the process to predict its systematic nature. After carefully and in-depth examining the full texts of the articles, 10 relevant papers were chosen and included in the review out of a total of 130 articles that were identified. The themes in each article were found using an inductive thematic approach. Six themes have been classified: tools for mentoring; communication, interaction or relation; the role of the supervisor; satisfaction; performance; and motivation or support. This study has a significant impact on the tools that can be used in the online supervision process.